Metacognitive strategy in solving mathematics problems, learning approach and mathematics achievement of students from a junior college - Lo, Chee Lin. (2009)
This study establishes the relationship between the metacognitive strategies in solving mathematics problems and mathematics achievement of students at a junior college, as well as learning approaches and their mathematics achievement. The independent variables involved are metacognitive strategies in solving mathematics problems, i.e. Orientation, Organisation, Execution and Verification Strategies, and learning approaches, i.e. Surface, Deep and Achieving Approaches. The dependent variable is the mathematics achievement. In addition, the independent variables are also investigated according to gender (i.e. male or female), course of study (i.e. Science, Arts or Commerce), mathematics ability (i.e. grade obtained in mathematics achievement test) and mathematics inclination (i.e. whether students are Further Mathematics or Mathematics C students).